ANALISIS PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN BERBELANJA DI BRASTAGI SUPERMARKET - Dede Ansyari Guci; Alric Alric; Darwin Darwin; Puspa Liza Ghazali (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Brastagi Supermarket is located in the heart of Medan and many consumers come to shop at this supermarket. The purpose of this study was to determine and examine the effect of service quality and product quality on customer satisfaction when shopping at Brastagi Supermarket. This research uses a quantitative approach. The type of research used is quantitative, the sampling technique for Brastagi Supermarket and Slovin amounted to 225 consumers and the sample of this study amounted to 144. The model used is multiple linear regression. The result is that service quality affects customer satisfaction at Brastagi Supermarket, product quality affects customer satisfaction at Brastagi Supermarket. Service quality and product quality affect customer satisfaction at Brastagi Supermarket.